Synchrotron X-ray tomographic imaging of embedded fossil invertebrates in Aboriginal stone artefacts from Western Australia: Implications for sourcing, distribution and chronostratigraphy. (August 2019) - Ward, I.; Key, M.M.; O'Leary, M.J.; Carson, A.; Shaw, J.; Maksimenko, A.
Abstract: Eocene fossiliferous chert is a distinctive rock used in the manufacture of stone artefacts commonly found in archaeological sites in southwestern Western Australia (WA). In this study, we employ non-destructive high-resolution X-ray computer tomographic (CT) imaging at the Australian Synchrotron to map and identify embedded bryozoan (and other) fossils within archival artefact samples and potential source material from offshore drill cores in the Perth Basin and from the Nullarbor Plain to the east. Analysis of synchrotron data confirmed the presence of Cellaria, Porina, Quadricellaria, Reteporella, Siphonicytara, Trigonopora, and Idmonea species in chert samples from as far afield as Exmouth Gulf in the north west of WA, Esperance in the south and inland as far as the Goldfields region of WA. This widespread distribution of fossiliferous chert over 1800 km is significantly greater than previously documented and the bryozoan fingerprinting of geological source and artefact material indicates that a potential source within the Eucla Basin located in the SW corner of WA cannot be discounted. In addition, the association of one chert artefact on Doole Island (Exmouth Gulf) with shell midden material dated between 2500 and 770 yr BP also questions the use of fossiliferous chert as a late-Pleistocene-early Holocene chronological marker. The advantages and limitations of synchrotron CT imaging for characterising and sourcing fossiliferous chert are also discussed, with further research warranted on the distribution and probable long-distance trade of this idiosyncratic material. Highlights: 3D Imaging and characterisation of bryozoans using Synchrotron analysis Reinforces the onshore over the offshore hypothesis for the origin of the chert Demonstrates the widespread range of fossiliferous chert artefacts across Australia